Resolvin E1's Antimicrobial Potential Against Aggregatibacter Actinomycetemcomitans - Abdullatif, Fahad A.; Almaarik, Basmah; Al-Askar, Mansour (Frontiers in Oral Health, 2022)
Background: Microorganisms along with host response play a key role in the development of periodontal and peri-implant infections. Advanced periodontal and peri-implant disease is most likely associated with bacterial plaque that triggers host immune response which eventually leads to destruction to the attachment apparatus and bone loss around the tooth or dental implant. A recent systematic review and meta-analysis revealed that Aggregatibacter actinomycetemcomitans had the highest association with peri-implantitis. Resolvin E1 (RvE1) is part of the specialized pro-resolving lipid mediator family biosynthesized from omega-3, polyunsaturated fatty acid (PUFA) and eicosapentaenoic acid (EPA). Although RvE1 is an established anti-inflammatory agent, it was found that it’s application as a treatment or as a preventive drug had an indirect effect on the subgingival microbiota of both rats and rabbits with experimental periodontitis. Aim: Evaluate the direct antimicrobial efficacy of RvE1 on Aggregatibacter actinomycetemcomitans bacteria. Materials and Methods: The study was divided in to three groups that will undergo minimum inhibitory concentration (MIC) against Aggregatibacter actinomycetemcomitans. The first group tested with RvE1 working concentration 5 ug/ml, the second group tested with Ethanol (EtOH) 10% as the working concentration and the final group is diluted in PBS as a positive control. The optical density (OD600) was used for comparison of bacterial growth between tested groups. Experiment was done in three biological replicates. Data analyzed using SPSS, result carried out by using One-way analysis of variance (ANOVA) followed by pos-hoc and Bonferroni, Using a minimum level of significance (P-value) of 0.05. Results: The MIC was 1.25 µg/ml and 5% for RvE1 and EtOH respectively. RvE1’s mean optical density (OD600) was (0.156 ± 0.021) and was significantly lower with all other groups (p-value < 0.01). The Ethanol group (mean OD600 0.178 ± 0.013) and the PBS group (mean OD600 0.1855 ± 0.022) did not reveal significant difference (p-value = 0.185). Conclusion: RvE1 demonstrated a significant antimicrobial activity against Aggregatibacter actinomycetemcomitans with an MIC of 1.25 µg/ml. RvE1 group showed a significant lower bacterial growth compared to the EtOH and PBS groups.